Manage your customer portfolio for maximum lifetime value : how converting customers to closer relationships, leveraging them, and defending them can drive future revenue and lower costs - Selnes, Fred; Johnson, Michael D. (Michael David) (MIT Sloan Management Review, 2022)
Setting goals regarding relationship conversion, leverage, and defense can drive future revenue and lower costs, but this work requires a clear understanding of the heterogeneity of customer needs and economies of scale as they emerge over time. To inform and act upon this understanding, companies need an integrated approach to customer portfolio management and customer portfolio lifetime value.